MARTINE's real-time local market simulation with a semantically interoperable society of multi-agent systems. (March 2023) - Santos, Gabriel; Gomes, Luís; Pinto, Tiago; Faria, Pedro; Vale, Zita
Abstract: There is a growing complexity, volatility, and unpredictability in the electric sector that hardens the decision-making process. To this end, the use of proper decision support tools and simulation platforms becomes essential. This paper presents the Multi-Agent based Real-Time INfrastructure for Energy (MARTINE) platform that allows real-time simulation and emulation of loads, resources, and infrastructures. MARTINE uses multi-agent systems that connect to physical resources and can represent additional simulated players that are not physically present in the simulation and emulation environment, enabling the creation of complex scenarios for testing and validation. MARTINE provides the seamless integration of real-time emulation with simulated and physical resources simultaneously in a unique simulation environment, which is only possible by supporting multi-agent systems. This work presents MARTINE's integration in a semantically interoperable multi-agent systems society developed for the test, study, monitoring, and validation of the power system sector. The use of ontologies and semantic web technologies eases the interoperability between the heterogeneous systems. The case study scenario demonstrates the use of MARTINE in simulating a local community electricity market that combines real-time data from physical devices with simulated data and the use of semantic web techniques to make the system interoperable, configurable, and flexible.